Exploring the Synergistic Effects of Smart School Platforms and Cloud CCTV on Safety and Pedagogical Effectiveness in Vocational Education: A Systematic Review - Norma; Chen Fang (The Indonesian Institute of Science and Technology Research, 2026)
This systematic review aims to synthesize the most recent evidence (2023-2025) on the integration of Smart School Platforms and Cloud CCTV systems in vocational education and training (VET), mapping their synergistic effects on pedagogical effectiveness and safety. Following the PRISMA 2020 protocol, a systematic search of the Google Scholar database identified 24 relevant peer-reviewed journal articles published between 2023 and 2025. These studies were analyzed to extract data on technological integration, outcomes, and challenges. The analysis of literature reveals a clear synergy. Smart School Platforms (e.g., AI-LMS, IoT classrooms) demonstrably enhance learning personalization, engagement, and cognitive outcomes. Cloud CCTV enables proactive safety monitoring and provides behavioral data. Critically, their integration creates a tension: the technologies that make environments safer and more data-informed also introduce ethical concerns regarding student privacy, autonomy, and the potential for a surveillance-based pedagogy. This review is the first to systematically synthesize the latest research (2023-2025) on the confluence of pedagogical and security technologies within VET. For VET institutions, the findings underscore the necessity of developing ethical frameworks and transparent policies to harness the benefits of this technological synergy while safeguarding student privacy and trust. This study provides evidence-based foundation for the responsible digital transformation of vocational education, directing future empirical research to explore this interplay in hands-on learning environments like workshops and labs.